Nuclear and Cellular Abnormalities of Erythrocytes in Response to Thermal Stress in Common Carp Cyprinus carpio - Shahjahan, Md.; Khatun, Most. Sabia; Mun, Mim Mostarin; Islam, S. M. Majharul; Uddin, Md. Helal; Badruzzaman, Muhammad; Khan, Saleha (Frontiers in Physiology, 2020)
As a consequence of global warming, increase of water temperature is likely to alter physiological functions of fish. Hence, we examined the effects of high temperature on blood glucose, hematological parameters (hemoglobin, Hb; red blood cell, RBC; and white blood cell, WBC), and nuclear and cellular structure of blood cells of common carp (Cyprinus carpio) after exposure to three temperature regimes (27, 31 and 35°C) for 14 days. Fish were sacrificed on 3, 7 and 14 days of exposure. The blood glucose level increased significantly in the fish exposed to 35°C compared to 27°C and 31°C. The Hb and RBC contents decreased but WBC increased significantly in the blood of fish exposed to 35°C compared to 27°C and 31°C at 7 and 14 days of exposure. Consequently, the frequencies of erythroblasts (Ebs), erythrocytic nuclear abnormalities (ENA) and erythrocytic cellular abnormalities (ECA) were found to be increased in the blood of fish exposed to 35°C compared to 27°C and 31°C. There was a significant increase in neutrophils and decrease in lymphocytes in the highest temperature (35°C). With increasing temperature, dissolved oxygen decreased but free CO2 increased significantly during the study period. The present study demonstrated that common carp are better adapted to 27°C and 31°C environmental temperatures, while the higher temperature 35°C is likely stressful to this fish species.